Study of optical and electrical properties of tin doped cobalt-phthalocyanine thin films prepared by thermal co-evaporation - Narin Tammarugwattana; Sukittaya Jessadaluk; Narathon Khemasiri; Sakon Rahong; Adirek Rangkasikorn; Supamas Wirunchit; Navaphun Kayunkid; Jiti Nukeaw (My University, 2018)
The aim of this research is to study the specific properties e.g. surface morphology, optical absorption as well as electrical conductivity of tin-doped cobalt-phthalocyanine (CoPc) thin film prepared by thermal co-evaporation. The concentration of tin metal dopant is controlled via evaporation rate during film's preparation. The change of tin quantity leads to the significant changes not only in morphology but also in molecular packing of the doped films. Moreover, the dramatic increase in both carrier mobility and carrier concentration should provide the enhancement in electrical conductivity of the doped films. By controlling the specific properties of the tin-doped CoPc thin film, the increasing efficiency of optoelectronic applications based on metal-phthalocyanine could be achieved.
Keywords: Electron Mobility; Organic Electronics and Photovoltaics